KONSEP PLURALISME AGAMA DALAM PERSPEKTIF DJOHAN EFFENDI (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
The Indonesian nation is rich in religious diversity. There are officially 6 recognized religions in Indonesia, namely, Islam, Protestant Christianity, Catholic Christianity, Hinduism, Buddhism and Confucianism. Every religion has its own concept of religious beliefs. Because of these differences, religion is accused of being the main cause in conflicts that have different religious concepts. Conflicts in the name of religion can be understood because of the public's lack of understanding of religious pluralism. One of the figures who fight for religious pluralism is Djohan Effendi. He is a prominent Indonesian Muslim intellectual and is included in 50 figures of the Jaringan Islam Liberal (JIL). In this thesis, the researcher focuses on Djohan Effendi's thoughts on Religious Pluralism. The type of research used is library research, the type of data is qualitative using two data sources, namely, primary data sources are the sources of books written by Djohan Effendi. As well as secondary data, namely, data obtained from books, manuscripts, articles and so on related to the problem. For data collection techniques, namely collecting data in the form of books, journals and information related to the problem. While the analysis technique of this research is using qualitative descriptive data analysis by using a historical approach to the characters and an interpretation approach to the thoughts of the characters. Researchers must read carefully, think carefully so that conclusions can be found. The result of the analysis of the research on the concept of religious pluralism in Djohan Effendi's perspective is that Djohan Effendi rejects religious absolutism and accepts religious pluralism. Djohan separates religion and religiosity. According to him, absolute religion cannot be reached by human knowledge. Only God can know the absolute religion itself. While the religion that humans say is not absolute religion, but diversity so that every religious human being may say that his religion is the most correct and saving.